INNOVATIVE APPROACHES OF REMOTE BANKINGTYPESSERVICES IN THE PROCESS OF TRANSFORMATION OF BANKS TO E-COMMERCE - Mamadiyarov Zokir Toshtemirovich (International Journal of Innovations in Engineering Research and Technology, 2021)
The article examines the future development trends of remote banking services in the development of e-commerce on thebasis of foreign experience. The author’s approaches to assessing the effectiveness of banking services, the development of remote banking services and their solutions